Komitmen Organisasi, Pengendalian Internal, Kesesuaian Kompensasi terhadap Kecurangan Pengelolaan Keuangan Desa dengan Moralitas Individu sebagai Variabel Moderasi - Neni Nurhayati (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2022)
This study aims to determine organizational commitment, internal control, and compensation suitability against fraudulent village financial management with individual morality  as a moderating variable in Kuningan Regency. In this study using descriptive and verification methods. The subjects of this study were village government officials consisting of village heads, secretaries, and financial officers at the village government in Ciwaru, Cibingbin, Darma, and Cibeureum sub-districts in Kuningan district. The sampling technique in this study is simple random sampling. The analysis test in this study used instrument test, classical assumption test, multiple linear regression test, MRA test, coefficient of determination test, hypothesis test using SPSS 20.0 program. The data obtained in this study were obtained from the field, namely the distribution of questionnaires. The results of this study indicate that, organizational commitment, internal control and compensation suitability  have a positive and significant effect on fraudulent village financial management. individual morality strengthens organizational commitment, internal control and compensation suitability against fraudulent village financial management.